Sumptuary law in Italy, 1200-1500 - Killerby, Catherine Kovesi, 1963- (Oxford historical monographs., 2002)
This is a study of Italian sumptuary laws through a chronological, geographical, and thematic survey of more than 300 laws enacted in over 40 cities throughout the peninsula.